Needle Stick Injuries: A study Among Health Care Workers Tertiary Care Centre Nepal - Bajracharya, Manjari; Bhandari, Sushila (Medical Journal of Shree Birendra Hospital, 2018)
Introduction: A needle stick injury is a percutaneous piercing wound typically set by a needle point but possibly also by other sharp instruments or objects commonly encountered by health care professionals because of the risk to transmitting blood borne diseases like Hepatitis B Virus (HBV), Hepatitis C (HCV) and Human Immuno Deficiency Virus (HIV). The aim of this study was to assess the prevalence, causes, awareness and knowledge regarding Needle Stick Injury among health care workers Tertiary Care Centre of Nepal. Methods: A descriptive cross sectional study was conducted in 350 staffs of Tertiary Care Centre Nepal, from June to August 2013. Data was collected through semi-structured self-administered questionnaire. All the collected data was processed and analyzed by using descriptive statistics namely the frequency and percentage. Results: The study showed that out of the 350 respondents, 65.1% had there medicinal years of practices extended to five years. Among the responses 44.8% mentioned, highest number of needle prick was observed when recapping the needles due to long working hours. About 64.6% respondents washed their hands with soap, water or other antiseptics for effective post exposure preventive measures and 24.9% had access to infection control protocol. Conclusions: Despite the awareness regarding needle stick injury and its preventive measures, health care workers are yet bound to face it often during their surgical or medicinal area of practice due to monotonous and long working hours.